2019
DOI: 10.3390/jfb10040056
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Shape and Composition of Star-Shaped Polymers and their Ability to Both Bind and Prevent Bacteria Attachment on Oral Relevant Surfaces

Abstract: In this study, we have prepared a series of 4- and 6-arm star-shaped polymers with varying molecular weight and hydrophobicity in order to provide insight into the role and relationship that shape and composition have on the binding and protecting of oral relevant surfaces (hydroxyapatite, HAP) from bacteria colonization. Star-shaped acrylic acid polymers were prepared by free-radical polymerization in the presence of chain transfer agents with thiol groups, and their binding to the HAP surfaces and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Bacterial adhesion can be promoted or prevented by adjusting the hydrophobicity of dental materials. Therefore, hydrophobicity plays an important role in oral bacterial adhesion [ 7 , 35 , 36 ]. The surfaces of supragingival and subgingival biofilms are different in the oral environment.…”
Section: Relationship Between Dental Materials Surface Properties And...mentioning
confidence: 99%
“…Bacterial adhesion can be promoted or prevented by adjusting the hydrophobicity of dental materials. Therefore, hydrophobicity plays an important role in oral bacterial adhesion [ 7 , 35 , 36 ]. The surfaces of supragingival and subgingival biofilms are different in the oral environment.…”
Section: Relationship Between Dental Materials Surface Properties And...mentioning
confidence: 99%
“…32 Since then, similar works were developed to apply this macromolecular engineering approach with other polymers including antimicrobial polypeptides. [32][33][34][35] Overall, starlike polypeptide were shown to enhance the antimicrobial efficacy: to access such star-shaped copolymers means preparing macromolecules incorporating of cationic and hydrophobic side chains. So far, no one has extended the use of this design to antibacterial polypeptoids.…”
Section: Synthesis and Characterization Of Star-like Poly( Peptoid)s Copolymersmentioning
confidence: 99%
“…Venault et al reported surface charge-driven antifouling coatings based on polyethyleneimine that resist bacterial attachment on dental carries, demonstrating that negatively charged polymers enhanced antifouling compared to neutral polymers. It is well documented that carboxylic acid-based polymers are self-adhesive to hydroxyapatite through ionic interactions between the carboxyl groups and the calcium of hydroxyapatite. Mortazavian et al tested the effect of molecular weight and hydrophobicity of polymers bound to hydroxyapatite, finding a reduced adhesion of a mixed culture of Actinomyces viscosus and Streptococcus oralis. Despite several attempts to immobilize antifouling moieties on dental-mimicking surfaces, few detailed studies examine the balance between the antifouling and adhesive groups and their effects on performance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, polyacrylic acid (PAA) has been used to coat hydroxyapatite [Ca 10 (PO 4 ) 6 (OH) 2 ] via interactions between the cationic calcium ions and anionic carboxylate groups in PAA. 40 Venault et al 41 reported surface charge-driven antifouling coatings based on polyethyleneimine that resist bacterial attachment on dental carries, demonstrating that negatively charged polymers enhanced antifouling compared to neutral polymers. It is well documented that carboxylic acid-based polymers are selfadhesive to hydroxyapatite through ionic interactions between the carboxyl groups and the calcium of hydroxyapatite.…”
Section: ■ Introductionmentioning
confidence: 99%